Testosterone is not associated with traits of optimism or pessimism: observational evidence from the prospective DETECT study - Kische, Hanna; März, Winfried (PLOS ONE, 2018)
Previous experimental research on testosterone (T) and psychological traits is inconclusive. Thus, we performed the first large-scale observational study of the association between T and dispositional optimism / pessimism.
Gesehen am 23.10.2019